Preserving and Transmitting for Religious Moderation through Pesantren: a Case Study of Pesantren Lirboyo, East Java, Indonesia - Muhamad Yasin; Muhammad Nabil Khasbulloh; Titis Thoriquttyas (International Journal of Religion and Social Community, 2025)
In order to lay the groundwork for religious moderation in Indonesia, this study uncovers the function and strategy of the Pesantren (Islamic Boarding School) in Indonesia. In terms of stigma, attitudes, and conduct, Pesantren's role is crucial in ending the chain of radical schools of thought. Pesantren, particularly salaf pesantren (traditional pesantren), are acknowledged as being among the oldest educational institutions that are rooted in local knowledge as well as the Indonesian culture. Pesantren Lirboyo Kediri is one of salaf pesantren that has scientifically constructed religious moderation from the past to the present. By using descriptive qualitative research approached institutionally normatively, data was collected through interviews and documentation. This research revealed that the construction of Islamic moderation which is built through the concept of an integrative curriculum at Pesantren Lirboyo Kediri is based on the salafiyah and ahlussunnah wa al-jamaah traditions. The curriculum in question is not only about presenting the material, but also learning methods and daily intra and extracurricular activities (adjustment, habituation, moderation). The dissemination of Islamic moderation at Pesantren Lirboyo Kediri is patterned on learning methods, student habituation and Islamic Boarding Schools activities such as bahtsul masail.